2010
DOI: 10.1007/s12032-010-9515-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PD-L1 in lung cancer may contribute to poor prognosis and tumor cells immune escape through suppressing tumor infiltrating dendritic cells maturation

Abstract: The immunohistochemical analysis was used to evaluate the expression of PD-L1 in 109 non-small cell lung cancer (NSCLC) tissues and para-tumor tissues. Associations between expressed PD-L1 and tumor histological types, degree of differentiation, and lymph node metastasis were calculated, and overall survival was assessed. Meanwhile, immunohistochemistry and immunofluorescence double labeling technique were performed to detect the expressions of PD-L1, CD1α, and CD83 on TIDC of 20 lung cancer tissues, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
372
15
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(410 citation statements)
references
References 27 publications
19
372
15
4
Order By: Relevance
“…25,[40][41][42] PD-1 and PD-L1 blockade has shown to prolong survival in patients with advanced lung cancer, 17,18,43 indicating that activation of the PD-1/ PD-L pathway inhibits tumor surveillance, thus implicating this pathway as an adverse prognostic factor. However, a recent study demonstrated that PD-L1 (CD274) expression at the protein and mRNA levels was associated with better clinical outcomes in patients with non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,[40][41][42] PD-1 and PD-L1 blockade has shown to prolong survival in patients with advanced lung cancer, 17,18,43 indicating that activation of the PD-1/ PD-L pathway inhibits tumor surveillance, thus implicating this pathway as an adverse prognostic factor. However, a recent study demonstrated that PD-L1 (CD274) expression at the protein and mRNA levels was associated with better clinical outcomes in patients with non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, several reports claimed that elevated PD-L1 expression was predictive of poor clinical outcomes in several cancers including non-small-cell lung cancer. 41,42 Furthermore, upon interaction with PD-1, PD-L1 contributed to an anti-apoptotic effect in tumor cells in a cytosolic domain-dependent manner, 44 indicating that PD-L1 expression in tumor cells might not only induce T-cell exhaustion but also inhibit tumor cell death. In our study, although increased number of CD8 + or PD-1 + tumor-infiltrating lymphocytes were associated with prolonged disease-free survival, a high ratio of PD-1 + /CD8 + tumor-infiltrating lymphocytes was associated with shorter diseasefree survival.…”
Section: Discussionmentioning
confidence: 99%
“…The high PD-L1 expression has been identified as a negative prognostic marker in melanoma [24], RCC [25], and lung cancer [26]. Additionally, PD-L1 upregulation has been detected in gastrointestinal malignancies, such as pancreatic, colorectal, and GC, correlating with poor prognosis [27,28].…”
Section: Pd-1/pd-l1 Expression and Patient Outcomementioning
confidence: 99%
“…Among some of the mechanisms already described to be involved in this scenario, there are known regulatory pathways, such as CTLA-4 and PD-1/PD-L1 pathways, the major negative coreceptor expressed on T-cells [160]. While PD-1-related mechanisms act mainly at later stages, CTLA-4 regulates Tcells activity in earlier stages of tumor growth.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%